PERAN TEKNOLOGI KOMUNIKASI DALAM MENINGKATKAN EFEKTIVITAS MEDIA PEMBELAJARAN PADA PENDIDIKAN JARAK JAUH (Studi Kasus: LMS Damel pada UIN SIBER SYEKH NURJATI CIREBON) - Muhammad Haidar; Dewi Murthosia; Lusi Febria Sari; Teguh Shaumantri (PT. Hasba Edukasi Mandiri, 2025)
This study aims to explore the role of communication technology in enhancing the effectiveness of learning media in distance education, specifically through the LMS Damel utilized by UIN Siber Syekh Nurjati Cirebon. The study employs a qualitative descriptive approach using interviews, observations, and documentation as methods for data collection. Findings indicate that LMS Damel effectively improves academic interaction, accessibility of learning materials, and the management of educational evaluation. Identified challenges include the quality of internet connectivity, limited technological resources, and varying student motivation in participating in online learning.